2007
DOI: 10.1016/j.ymgme.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and tissue distribution of intravenously administered agalsidase alfa

Abstract: Abstractα-Galactosidase A is the lysosomal hydrolase that is deficient in patients with Fabry disease. Intravenous infusion of agalsidase alfa, a preparation of α-galactosidase A, is used for enzyme replacement therapy (ERT) in patients with Fabry disease. Although ERT appears to show some beneficial effects, most patients show only a modest response. We investigated using immunohistochemistry the relative tissue and cellular distribution of agalsidase alfa after a single intravenous injection in a mouse knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…This is consistent with other studies of long-term ERT for FD, where persistent storage of GL3 has been demonstrated in vascular smooth muscle, stromal fibroblasts, pericytes and skeletal muscle fibres (Keslova-Veselikova et al 2008) and subtotal removal demonstrated in cultured skin fibroblasts (Askari et al 2007). GL3 clearance varies between different cell types (Murray et al 2007). Renal, myocardial and dermal endothelium clears after 5-6 months of ERT, and sustained clearance from vascular endothelium has been demonstrated after 30-36 months of ERT (Eng et al 2001;Wilcox et al 2004;Keslova-Veselikova et al 2008;Thurberg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies of long-term ERT for FD, where persistent storage of GL3 has been demonstrated in vascular smooth muscle, stromal fibroblasts, pericytes and skeletal muscle fibres (Keslova-Veselikova et al 2008) and subtotal removal demonstrated in cultured skin fibroblasts (Askari et al 2007). GL3 clearance varies between different cell types (Murray et al 2007). Renal, myocardial and dermal endothelium clears after 5-6 months of ERT, and sustained clearance from vascular endothelium has been demonstrated after 30-36 months of ERT (Eng et al 2001;Wilcox et al 2004;Keslova-Veselikova et al 2008;Thurberg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, detailed information was published on the relative tissue and cellular distribution of agalsidase alfa in a mouse knockout model of AFD (Murray et al 2007). Specific immunostaining for the recombinant enzyme was found in the liver, kidney, heart, testes, adrenal gland, spleen and bone marrow.…”
Section: Agalsidase Alfa and Special Considerationsmentioning
confidence: 99%
“…The reduction of Gb3 in the different groups of patients was found to be similar, and the authors concluded that, based on the effects on plasma Gb3 levels, increased dosages or frequency of dosing were not superior to the recommended dose of 0.2mg/kg every other week. Murray et al (2007) [48] studied the cellular and tissue distribution of agalsidase alfa in Fabry knock-out mice. Six mice received, by injection, a dose of 0.5mg of enzyme/kg body weight, and six other mice received vehicle only.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%